First‐line PD‐1/PD‐L1 inhibitors plus chemotherapy versus bevacizumab plus chemotherapy for advanced non‐squamous non‐small cell lung cancer: A Bayesian network meta‐analysis of randomized controlled trials. (22nd March 2022) - Zhai, Jinzhao; Lu, Jiangyue; Zhang, Zhibo; Wang, Yuan; Li, Xiaoyan; Zhang, Sujie; Mu, Shuai; Zhi, Xiaoyu; Ge, Xiangwei; Lu, Di; Hu, Yi; Wang, Jinliang
Abstract: Chemotherapy in combination with immune checkpoint inhibitor (ICI) or bevacizumab has demonstrated a superior effect for non‐squamous non‐small cell lung cancer (NS‐NSCLC). There are still few randomized controlled trials (RCTs) investigating the differences between ICI plus chemotherapy (ICI‐chemotherapy) and bevacizumab plus chemotherapy (Bev‐chemotherapy) in first‐line treatment of NS‐NSCLC. We identified RCTs in databases and conference abstracts presented at international conferences by Sep 1, 2021. Bayesian network meta‐analysis was performed using randomized effect consistency model to estimate hazard ratio (HR) and odds ratio (OR). The outcomes included overall survival (OS), progression‐free survival (PFS), overall response rate (ORR), and grade ≥ 3 treatment‐related adverse events (TRAEs). Fifteen RCTs (17 articles) of 6561 advanced NS‐NSCLC patients receiving ICI‐chemotherapy, Bev‐chemotherapy, or chemotherapy at first‐line were eligible for analysis. NMA results showed that first‐line ICI‐chemotherapy prolonged OS (HR 0.79, 0.66–0.94) in patients with advanced NS‐NSCLC compared with Bev‐chemotherapy, while no differences were in PFS, ORR, and grade ≥ 3 TRAEs ( p > 0.05). Ranking plots suggested that ICI‐chemotherapy had the most probability to offer the best OS (probability 0.993), PFS (probability 0.658), and ORR (probability 0.565), and Bev‐chemotherapy had the most risks of grade ≥ 3 TRAEs (probability 0.833). Therefore, our findings showed that first‐line ICI‐chemotherapy was associated with better OS than Bev‐chemotherapy in patients with advanced NS‐NSCLC, and more clinical trials are warranted to confirm these results. Abstract : ICI‐chemotherapy and bev‐chemotherapy are superior to chemotherapy alone for previous untreated NS‐NSCLC. ICI‐chemotherapy may have long‐term effect and prolong survival compared with bev‐chemotherapy without more severe TRAEs.